ANALISIS KINERJA KEUANGAN PADA PT GARUDA MANDIRI BETON DI BALIKPAPAN (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Siprianus Paskalis Feko 2018, Financial Performance Analysis of PT Garuda Mandiri Beton in Balikpapan under the guidance of Mr. Irwansyah and Mrs. Ferry Diyanti.The formulation of the problem in this research is how the performance of PT Garuda Mandiri Beton in Balipapan during 2014 until 2016 seen from the ratio of liquidity, solvency ratio, and profitability ratios.The purpose of this research is to know and analyze the financial information of PT Garuda Mandiri Beton in Balikpapan during 2014 until 2016 period in terms of liquidity ratio, activity ratio, ratio, and solvency ratio.